2021
DOI: 10.1021/acs.energyfuels.1c00493
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of High-Energy Cathode Materials of Metal-Ion Batteries: Control Strategies and Synthesis Protocols

Abstract: Metal-ion batteries, especially lithium-ion batteries (LIBs), sodium-ion batteries (SIBs), and potassium-ion batteries (PIBs), have emerged as promising electronic devices for energy conversion and storage. To satisfy the upsurging demand for high energy density, cathode materials as the determining component in the battery system are driven to deliver higher capacities by either extracting more active metal ions (Li+, Na+, and K+) or increasing the operating voltage. However, serious side reactions of cathode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…Since it consumes a lot of Na, the electronic conductivity decreased, and the electrochemical property was compromised. 195 Many researchers suggested applying coating modifications to the surface of cathode materials, such as carbon coating, 196 polymer coating, 197 and inorganic compound coating 198 to solve these issues. The cathode material can avoid reacting with the air and electrolyte by having a coating layer on its surface that can stop Na from escaping.…”
Section: Techniques For Improving the Electrochemical Performance Of ...mentioning
confidence: 99%
“…Since it consumes a lot of Na, the electronic conductivity decreased, and the electrochemical property was compromised. 195 Many researchers suggested applying coating modifications to the surface of cathode materials, such as carbon coating, 196 polymer coating, 197 and inorganic compound coating 198 to solve these issues. The cathode material can avoid reacting with the air and electrolyte by having a coating layer on its surface that can stop Na from escaping.…”
Section: Techniques For Improving the Electrochemical Performance Of ...mentioning
confidence: 99%
“…In contrast, the wet chemical method is considered to be an ideal surface coating method due to its simple synthesis method, low cost and environmental friendliness, However, it should be noted that the cathode material is usually sensitive to moisture, so organic solvents such as ethanol should be selected instead of deionized water. [82] Liu et al [83] used a wet chemical method to coat the surface of a P2À Na 2/3 [Ni 1/3 Mn 2/3 ]O 2 electrode with Al 2 O 3 and investigated the reasons for the capacity decay of the electrode. It was found that the harmful reaction between the electrode and the electrolyte under high voltage led to the peeling of the metal oxide layer and thus resulted in poor cycling stability.…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%
“…Wet chemical method : Despite the outstanding performances of surface coatings using ALD technology, the precursors used as coating materials are usually costly and poisonous, which not only increases the manufacturing costs of coated electrodes but also pollutes the environment. In contrast, the wet chemical method is considered to be an ideal surface coating method due to its simple synthesis method, low cost and environmental friendliness, However, it should be noted that the cathode material is usually sensitive to moisture, so organic solvents such as ethanol should be selected instead of deionized water [82] …”
Section: Metal Oxide Coatingsmentioning
confidence: 99%
“…It consumes considerable Na + , so the electronic conductivity declined and the electrochemical property was impaired. [ 47 ] To address these problems, many researchers proposed to carry out coating modifications on the surface of cathode materials, such as carbon coating, [ 48 ] inorganic compounds coating, [ 49 ] and polymer coating. [ 50 ] The coating layer on the surface of the cathode material can prevent Na + from escaping and the cathode material from reacting with the air and electrolyte.…”
Section: Surface Coatingmentioning
confidence: 99%